2013
DOI: 10.1016/j.stem.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

The Epidermis Comprises Autonomous Compartments Maintained by Distinct Stem Cell Populations

Abstract: SummaryThe complex anatomy of the epidermis contains multiple adult stem cell populations, but the extent to which they functionally overlap during homeostasis, wound healing, and tumor initiation remains poorly defined. Here, we demonstrate that Lrig1+ve cells are highly proliferative epidermal stem cells. Long-term clonal analysis reveals that Lrig1+ve cells maintain the upper pilosebaceous unit, containing the infundibulum and sebaceous gland as independent compartments, but contribute to neither the hair f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
353
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(378 citation statements)
references
References 51 publications
24
353
0
1
Order By: Relevance
“…10 Indeed, once we focused our analyses on the wound basal layer, we observed that HF-derived cells, including bulge-derived cells, actually increased in the wound over time. Altogether, these findings suggest that cellular position within the wound epithelium-basal vs. suprabasal-may affect whether a cell persists.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…10 Indeed, once we focused our analyses on the wound basal layer, we observed that HF-derived cells, including bulge-derived cells, actually increased in the wound over time. Altogether, these findings suggest that cellular position within the wound epithelium-basal vs. suprabasal-may affect whether a cell persists.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with these findings, previous studies have indicated that mobilized bulge cells can be retained in the HF infundibulum, 15,36 and that HF isthmus-derived cells appear to migrate farther into the wound than do lower bulgederived cells. 10 It is important to note that these observations might also be explained if bulge-derived cells exhibit innate differences in proliferation or migration rates that delay their entry into the site of injury. Nonetheless, the relative absence of bulgederived cells in the middle of the wound might provide an extrinsic explanation for why these cells reportedly do not contribute to HF neogenesis, which occurs only at the wound center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lineage tracing studies using transgenic mouse models have revealed a surprising degree of compartmentalization, with the turnover of hair follicle, sebaceous gland, and interfollicular epidermis (IFE) maintained by independent stem-cell populations (24). In IFE, proliferation is confined to…”
Section: Deep Sequencing As a Clonal Marker In Human Epidermismentioning
confidence: 99%
“…stem cell | perineural niche | touch dome | Merkel cell | Hedgehog T he skin is one of several tissues in which the epithelium is organized into specialized regions, and each compartment is maintained by lineage-specific stem cells (1). Epithelial-mesenchymal interactions are classically regarded as critical signals in establishing and maintaining epidermal lineage compartments (2).…”
mentioning
confidence: 99%